Naturezas emergentes: ações comunicativas para reafirmar a vida - Santos, Ariane Alves dos (2021)
In recent decades, a significant amount of research has problematized the notion of nature. More than a purely conceptual debate, it is a reflection with political, economic, social and ecological implications. The aim of this thesis is to put together some authors who have been guided by this debate (Coccia, Greiner and Katz, Lapoujade and Latour, among others) by affirming the non-duality between nature and culture; and, at the same time, to identify how some works of contemporary visual artists not only collaborate with these discussions, but also establish other paths of perception/reflection that make us recognize the complex relations between body and environment, and the alliances between theory and practice from the experiences. Along the way, it has become fundamental to understand how the processes of semiosis in art can contribute to the debates about the perception and communication of the singular body in the environments through which it transits. The corpus of the artistic experiments was composed of installations and interventions performed by WalmorCorrêa, Nils Udo, Cildo Meireles, Ana Amélia Genioli, Ahmad Nadalian among others. The works gathered here have contributed to affirming the notion of a nonsubstantiating, universal or pre-existing nature. At the end, we have concluded that these processes of creation constitute themselves as production forces of singularization, by activating temporalities, becomings and heterogeneous transformations that mark the processes of affirmation of life